Effect of annealing on etch rate of Nuclear Track Detector CR-39 - Rasha wael; Mushtaq Al-Jubbori (College of Education for Pure Sciences, 2023)
The purpose of this paper is to investigate the impact of annealing on bulk etch rate (VB), which is calculated using the thickness measurement method. A 600- micro meter-thick CR-39 detector, divided into four samples (1 x 1 cm2), was vertically irradiated by alpha particles from a 241Am source at 2.6 MeV energy. The three samples were annealed at 100-140 C in 20 C increments using Memmert U4079142. All samples were etched in a 6.25 N NaOH solution at 701 C in a Memmert W200 water bath. The periodic etching time was 6 hours, every 0.5 hours. The etched image was captured using a camera (MADC_5A) attached to a microscope (XSZ-H Series Biological Microscope). The bulk etch rate and diameters increase with increasing annealing temperatures. The new method used in this paper to calculate the experimental track length is based on the relation between track length and track diameter obtained from track-test software.